The specificity of the investment in land as in real estate - Remeikienė, Rita; Gasparėnienė, Ligita; Ginevičius, Romualdas (International Journal of Strategic Property Management, 2019)
The main purpose of this article is to identify the motives of investing in land and arable land and determine the choices of such investment. The empirical research, based on the method of expert evaluation, fills the gap of the investment in land observed in scientific literature. The expert evaluation has allowed to develop a profile of a land investor, identify the determinants of the value of land and arable land and clarify the motives of investing in land in a small open economy (the trends in one small economy may reflect similar trends in other small open economies, for instance, Latvia or Estonia). The novelty of the article lies in the disclosure of the general and Lithuania-inherent land investment risks and assessment of the impact of the main land value determinants. The practical implications of the article lie in submission of the guidelines to real estate policy and practice makers, investors, real estate developers, buyers and other parties concerned that want to get a better understanding of the expediency or inexpediency of the investment in land.